STEM-06. THE ROLE OF IFITMs IN MAINTAINING GLIOMA STEM CELLS. (9th November 2020) - Nita, Erisa; Nekulova, Marta; Brennan, Paul M; Ball, Kathryn
Abstract: Glioblastoma, one of the most lethal and heterogeneous primary brain tumours, contains cellular hierarchies with both quiescent and self-renewing glioblastoma stem cells (GSCs). GSCs contribute to a lack of progress in patient survival as they appear to have an innate resistance to both chemotherapy and radiotherapy. The aim of this study is to elucidate how constitutive expression of interferons (IFNs) and their downstream signalling pathways maintain GSCs thereby supporting treatment resistance and tumour reoccurrence. To understand the mechanism of action of a subset of IFN regulated genes, originally characterized as a signature for radiation and chemotherapy resistance (IRDS), a panel of patient derived GSCs was generated and manipulated using CRISPR/Cas9 gene-editing. Phenotypic changes in growth, viability and drug resistance were characterised and linked to molecular level events using transcriptomic and proteomic techniques. Using this approach, in conjunction with patient tissue analysis, signalling under basal as well as IFN-activated conditions was studied in the context of GSC status. Immunohistopathology of a glioma tissue micro-array identified an increased expression of IFN induced transmembrane receptors (IFITMs), which co-localised with Nestin, around the blood vessels suggesting that IFITM positive cells were in the stem cell niche. Further analysis showed the presence of IFITM1 and IFITM3 in GSCs and established that loss of IFITMs function impacted on growth rate and cell cycle progression as well as treatment sensitivity. By using wild-type and gene-edited GSC to focus on the relationship between IFITM1 and IFITM3, we have compelling phenotypic and molecular evidence that IFN-induced changes in the localisation of IFITMs impact on the ability of stem cells to 'escape' normal growth control mechanisms. Taking into consideration the constitutive expression of interferons in the tumour microenvironment, our study provides evidence that IFITMs regulate GSC self-renewal and are involved in maintaining a quiescent population which can escape chemotherapy.